Tuesday

July 29, 2014

July 29, 2014

Posted by **Daniela** on Sunday, November 4, 2012 at 8:04pm.

- math -
**Steve**, Monday, November 5, 2012 at 12:58amusing implicit differentiation,

6x + 2y + 2xy' + 2yy' = 0

when x=1, y=-1, so plug them i:

6 - 2 + 2y' - 2y' = 0

Note that there is no solution, so the tangent to the curve is vertical. y' is not defined.

Looking at dx/dy,

6xx' + 2x + 2yx' + 2y = 0

6x' + 2 - 2x' - 2 = 0

4x' = 0

x' = 0

just as we suspected: dx/dy=0, so the slope is vertical.

**Related Questions**

Algebra - Please look at the following simplification of an algebraic expression...

Algebra - Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a...

Math - Can 2xy - y - 1 be factored out? How? about all you can do is take the ...

Algebra - I thought number 4 on this list was incorrect but didn't know how to ...

Math - What is the value of the expression 2xy when x=-2,y=3

Math - If x=4 and y=-2, the value of 1/2xy^2 is..? i think it's 8.

Calculus - Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of ...

math - Let x = 2 and y = 4. Find the value of the given capital letter. N = x2...

Liberal Arts Math - factor the polynomial completely: 2xy-3y-40x+60 2xy-40x-3y+...

calc - let y be the function of x defined implicitly by the equation x^2 -2xy +...